Integration of the Qur’ānic worldview with the natural sciences: answering the long call for (Islamic) secondary schools - Hassan, Nor Jannah (IIUM Press, 2015)
The question of integration in the education of the ummah has been a top agenda among Islamic intellectuals and activists since the post-colonial period whose secular-humanism and atheistic-modernism left Muslims with the legacy of a dichotomous education. Many contemporary Islamic educational institutions in the Muslim world have established since then, each with their somewhat distinctive modes of integration. Integration is a loose terminology, in so far as Islamic education is concerned. How much have the Muslims progressed toward true integration of the Qur’ānic Worldview in the curricula of the natural sciences in secondary Islamic education, the stage whereby students are at critical stages of their cognitive, affective, spiritual, social and ethical developments? This paper presents a brief qualitative report on the findings from field researches that probed at a few samples of integration modes at a number of Islamic secondary schools in Malaysia and Indonesia; in relation to the ideal where integration constitutes a full merger, an organic fusion between knowledge that is revealed and that which is acquired through reason. In an effort to understand Western modern science, the paper skims through the worldviews that have brought about the natural sciences to its current plinth. It proposes a model for Islamic secondary education where the Natural Sciences undergo a discreet but holistic reconstruction, reinterpretation, and redirection from the framework of, and organically infused with the Qur’ānic worldview; whilst enriching ‘Islamic studies’ with a good grounding in and appreciation of the natural sciences.